Reproductive Aging in Caenorhabditis elegans: From Molecules to Ecology - Scharf, Andrea; Pohl, Franziska; Egan, Brian M.; Kocsisova, Zuzana; Kornfeld, Kerry (Frontiers in Cell and Developmental Biology, 2021)
Aging animals display a broad range of progressive degenerative changes, and one of the most fascinating is the decline of female reproductive function. In the model organism C. elegans, hermaphrodites reach a peak of progeny production on day 2 of adulthood and then display a rapid decline; progeny production typically ends by day 8 of adulthood. Since animals typically survive until day 15 of adulthood, there is a substantial post reproductive lifespan. Here we review the molecular and cellular changes that occur during reproductive aging, including reductions in stem cell number and activity, slowing meiotic progression, diminished Notch signaling, and deterioration of germline and oocyte morphology. Several interventions have been identified that delay reproductive aging, including mutations, drugs and environmental factors such as temperature. The detailed description of reproductive aging coupled with interventions that delay this process have made C. elegans a leading model system to understand the mechanisms that drive reproductive aging. While reproductive aging has dramatic consequences for individual fertility, it has also consequences for the ecology of the population. Population dynamics are driven by birth and death, and reproductive aging is one important factor that influences birth rate. A variety of theories have been advanced to explain why reproductive aging occurs and how it has been sculpted during evolution. Here we summarize these theories and discuss the utility of C. elegans for testing mechanistic and evolutionary models of reproductive aging.